Notch Signaling and MicroRNA: The Dynamic Duo Steering Between Neurogenesis and Glioblastomas - Javed, Zeeshan; Khan, Khushbukhat; Raza, Qamar; Sadia, Haleema; Ahmad Shah, Faiez; Ahmad, Touqeer; Bentivegna, Angela; Bazzoni, Riccardo; Setzer, William N.; Alshehri, Mohammed M; Sharifi-Rad, Javad; Daştan, Sevgi Durna (Cellular and Molecular Biology, 2021)
Notch signaling is an evolutionary conserved pathway that plays a central role in development and differentiation of eukaryotic cells. It has been well documented that Notch signaling is inevitable for neuronal cell growth and homeostasis. It regulates process of differentiation from early embryonic stages to fully developed brain. To achieve this streamlined development of neuronal cells, a number of cellular processes are being orchestrated by the Notch signaling. Abrogated Notch signaling is related to several brain tumors, including glioblastomas. On the other hand, microRNAs are small molecules that play decisive role in mediating and modulating Notch signaling. This review discusses the crucial role of Notch signaling in development of nervous system and how this versatile pathway interplay with microRNAs in glioblastoma. This review sheds light on interplay between abrogated Notch signaling and miRNAs in the regulation of neuronal differentiation with special focus on miRNAs mediated regulation of tumorigenesis in glioblastoma. Furthermore, it discusses different aspects of neurogenesis modulated by the Notch signaling that could be exploited for the identification of new diagnostic tools and therapies for the treatment of glioblastoma.